Spontaneous in the Llay-Llay Hospital and their relation to mothers’s agricultural labors - Contreras-Levicoy, Juan; Astorga, Erika; Castro, Rodrigo; Yentzen, Galdys; Cumsille, Miguel (Revista Chilena de Salud Pública, 2005)
Pesticides are chemical substances frequently used in agricultural areas of our country. It is a well established fact that these substances can be harmful to the health, not only of agricultural workers, but also to that of their offspring. The objective of this paper is that of studying the relation between spontaneous abortions and the agricultural occupation of the mother. A descriptive study was carried out assembling the clinical records of those patients presenting spontaneous abortion registered in the maternity book of procedures of the San Francisco de Llay-Llay Hospital between January 2002 and December 2003. The incidence of spontaneous abortion is calculated comparing it to the last available national figures, and the percentage of agricultural occupation of the mother in relation to the 15 year old and over female population of the same geographic area, according to the 2002 Census. The Z test was performed for comparison of proportions and confidence intervals for the ratio between incidence densities. The incidence rate for spontaneous abortion was 81.02 cases/ 1, 000 live-newborn registrations (RNV) versus 9.5 cases/ 1, 000 live-born registrations in Chile 1996, granting an incidence ratio of 8.5 (CI=6. 72-10. 65). The percentage of agricultural occupation is higher than the female 15 year old and over population of the same geographic area (p<0. 0001 ). The risk of .spontaneous abortion occurring in Llay-Llay or Catemu is higher than in the rest of the country. The agricultural occupation is related to a higher risk of 5pontaneous abortion, probably due to the exposure to pesticides.